The rise and progress of printing - Martin, E. Madge (My University, 1908)
Introduction: “Printing is the process of taking impressions – generally on paper in ink – of printing types of designs, drawings or photographic prints, which have been previously cut, etched, drawn or engraved on some solid surface.” Printing on paper in ink may be divided into four kinds: namely, typeography, xylography, lithography and copper or steel plate.
Citation: Martin, E. Madge. The rise and progress of printing. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Printing; Writing; History; Paper; Graduating theses; Senior theses; Theses